2016
DOI: 10.3390/insects7040074
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Tolerance to Silica-Based Desiccant Dusts in a Pyrethroid-Resistant Strain of Cimex lectularius (Hemiptera: Cimicidae)

Abstract: Insecticide resistance in bed bugs (Cimex lectularius and Cimex hemipterus) has become widespread, which has necessitated the development of new IPM (Integrated Pest Management) strategies and products for the eradication of infestations. Two promising options are the diatomaceous earth and silica gel-based desiccant dusts, both of which induce dehydration and eventual death upon bed bugs exposed to these products. However, the impact of underlying mechanisms that confer resistance to insecticides, such as cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 55 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…Penetration resistance also works in combination with other resistance mechanism(s), as it has been hypothesized that decreased cuticular penetration could help to ‘buy more time’ for detoxifying enzymes to metabolize the insecticide or to allow the insect to excrete the insecticide before it reaches its target [90, 98]. Penetration resistance has been reported in various insect pests, including the house fly Musca domestica (L.) [98100], the German cockroach B. germanica [2, 101], the dengue mosquito Aedes aegypti (L.) [102], and the common bed bug, C. lectularius [94, 95, 103]. …”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…Penetration resistance also works in combination with other resistance mechanism(s), as it has been hypothesized that decreased cuticular penetration could help to ‘buy more time’ for detoxifying enzymes to metabolize the insecticide or to allow the insect to excrete the insecticide before it reaches its target [90, 98]. Penetration resistance has been reported in various insect pests, including the house fly Musca domestica (L.) [98100], the German cockroach B. germanica [2, 101], the dengue mosquito Aedes aegypti (L.) [102], and the common bed bug, C. lectularius [94, 95, 103]. …”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…Diatomaceous earth has been perceived as less toxic to mammals and a more sound option for bed bug control [ 20 , 40 , 41 ]. Several laboratory studies have reported high efficacy of DE against bed bugs [ 29 , 31 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These responses might be behavioral adaptations that would decrease the pickup of dust particles [ 33 ]. In addition, a recent study reported that a multiresistant bed bug population with cuticular thickening exhibited tolerance to sublabel rates of silica gel-based dusts (CimeXa) [ 41 ]. These findings are worrisome given the fact that these mechanisms might confer cross resistance across other nonrelated insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…When bed bugs were exposed to CimeXa insecticide dust during a choice bioassay and a forced-exposure bioassay, 95% mortality was achieved after 1 day, and 100% mortality was observed after 5 and 10 days [ 20 ]. In another laboratory study, CimeXa insecticide dust at the label rate produced 100% mortality in highly pyrethroid-resistant and insecticide-susceptible strains of bed bugs within 3–4 days [ 21 ]. Ninety-eight percent mortality was achieved after 1 day when silica gel dust, in a water solution, was applied to bed bugs that were moderately resistant to pyrethroids [ 22 ].…”
Section: Introductionmentioning
confidence: 99%